Selective targeting of kinesin on lipid droplets in the liver reduces plasma lipids - Subham Kumar Tripathy; Archisman Mahapatra; Ojal Saharan; Hindol Chatterjee; Neelanjana Sengupta; Siddhesh Kamat; Sreelaja Nair; Roop Mallik (Proceedings of the National Academy of Sciences, 2026)
The liver controls plasma lipids by secreting lipid-rich very low density lipoproteins (VLDL) into blood. Inside hepatocytes in the liver, Lipid Droplets (LDs) are transported to the Smooth Endoplasmic Reticulum by kinesin-1 motors, where they are catabolized to supply lipids for VLDL assembly. Here we find that kinesin-1 uses its tail domain to bind the monolayer phospholipid membrane of LDs, but alternative mechanisms to bind cellular organelles with bilayer membranes. A peptide corresponding to the tail domain of kinesin-1 therefore competes with and removes kinesin-1 selectively from LDs with minimal effect on other organelles. Delivery of lipids for VLDL assembly is consequently reduced, causing a remarkable reduction of ~50% of secreted lipids (triglycerides and cholesterol) in cell culture. Strikingly, the peptide causes no unwanted accumulation of lipids inside cells because it redistributes LDs across the cell, enhancing LD-to-mitochondria lipid trafficking for mitochondrial lipid utilization. Further, we show that egg-liposomes can be used to orally deliver the kinesin tail domain peptide to zebrafish. The peptide accumulates in the zebrafish liver, and reverses diet-induced hyperlipidemia to bring zebrafish back to a normolipidemic state. Reflecting its effects in cell culture, the peptide causes no unwanted hepatic accumulation of lipids, no toxicity, and no developmental or behavioral defects in zebrafish. Using a peptide to displace proteins (e.g., kinesin) selectively from LDs provides a radically different approach against lipid disorders. This monolayer-vs.-bilayer strategy can potentially be extended to target other LD-bound proteins that function as key regulators of Lipid metabolism.